Spatio-temporal dynamics of jerky flow in high-entropy alloy at extremely low temperature. Issue 2 (17th January 2021) - Pu, Z.; Xie, Z. C.; Sarmah, R.; Chen, Y.; Lu, C.; Ananthakrishna, G.; Dai, L. H.
ABSTRACT: Despite a large body of literature, mechanisms contributing to low temperature jerky flow remain controversial. Here, we report a cross-over from a smooth at room and liquid nitrogen temperatures to serrated plastic flow at 4.2 K in high-entropy CrMnFeCoNi alloy. Several complimentary investigations have been carried out to get a coherent physical picture of low temperature jerky flow in these alloys. Microstructural characterisations at 77 K and 4.2 K show that the number of Lomer-Cottrell (L-C) locks at 4.2 K is much higher than that at 77 K, inducing stronger barriers for dislocation glide at 4.2 K. A stability analysis shows that the jerky flow results from an interaction between dislocation inertial motion with L-C locks. The instability results from a competition between inertial and viscous time scales characterised by a Deborah number. A detailed nonlinear time series analysis of experimental serrated stress signals shows that jerky flow is chaotic characterised by the existence of a finite correlation dimension and a positive Lyapunov exponent. Further, the minimum degree of freedom required for the chaotic dynamics turns out to be four, consistent with four collective modes degrees of freedom used in our model equations. These results highlight the crucial ingredients for jerky flow at liquid helium temperatures.